Temperature Changes in Gutta-Percha and Resilon Cones Induced by a Thermomechanical Compaction Technique - Sant'Anna-Junior, Arnaldo [UNESP]; Tanomaru-Filho, Mario [UNESP]; Hungaro Duarte, Marco Antonio; Santos Nunes Reis, Jose Mauricio [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Elsevier B.V., 2009)
Introduction: The aim of this study was to assess temperature changes in conventional gutta-percha, thermoplastic gutta-percha, and Resilon cones by using thermomechanical compaction technique. Methods: The root canals of extracted human teeth were placed in resin blocks and sectioned. After root canal preparation, cavities perforating the lingual wall were prepared at 4 and 8 mm from the apex, and K-type thermocouples coupled to a digital temperature meter were inserted until reaching the root canal. After placement of the main cone and accessory cones of each material assessed, a #45 thermomechanical compactor was used at 10,000 rpm. Data were analyzed by using analysis of variance and Tukey test for paired comparisons (P < .05). Results: A significant difference was observed between initial and maximum temperatures (mean increase, 5 degrees C-8 degrees C) with all materials (P < .05). The 3 materials showed similar temperature changes (P > .05). Changes in the apical third were higher when compared with the cervical third (P < .05). Conclusions: Our results suggest that gutta-percha and Resilon present similar temperature changes during thermomechanical compaction. (J Endod 2009;35:879-882)
Keywords: Gutta-percha; Resilon; thermal properties